2012
DOI: 10.1038/aja.2011.134
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome after intracytoplasmic sperm injection with strontium oocyte activation in a globozoospermic patient

Abstract: We present here a case report of a globozoospermic patient whose partner became pregnant after intracytoplasmic sperm injection (ICSI) with assisted oocyte activation (AOA). Globozoospermia is characterized by the presence of 100% roundheaded spermatozoa lacking an acrosome. The lack of the acrosome, which renders spermatozoa unable to bind to the zona pellucida or fuse with the oocyte oolemma, is considered to be the cause of infertility in these patients. 1 The introduction of ICSI provided a possible solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Only one case of oocyte activation using strontium chloride (10 m m , 10 min) was published in 2012. Twenty percent of the oocytes fertilized and a twin birth occurred (Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Only one case of oocyte activation using strontium chloride (10 m m , 10 min) was published in 2012. Twenty percent of the oocytes fertilized and a twin birth occurred (Yang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, ICSI combined with AOA was considered as an efficient procedure for treatment of men with globozoospermia. Although, some papers reported successful fertilisation and pregnancy after ICSI‐AOA in these individuals, but there are studies that reported conflicting results (Check, Levito, Summers‐Chase, Marmar, & Barci, ; Dirican et al., ; Egashira, Murakami, Haigo, Horiuchi, & Kuramoto, ; Eldar‐Geva et al., ; Kamiyama et al., ; Karaca, Akpak, Oral, Durmus, & Yilmaz, ; Kim, Cha, Park, & Gye, ; Kyono et al., ; Rybouchkin, Van der Straeten, Quatacker, De Sutter, & Dhont, ; Tejera et al., ; Yang et al., ; Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have not been any reports of genetic analysis in humans born following AOA treatment. The long‐term effect of the potential toxicity of AOA on humans remains unknown (Yang et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Fertilisation and pregnancy rates in these reports have always been low, despite the application of ICSI. Therefore, activations of the oocyte by chemical (Rybouchkin et al ., ; Kim et al ., ; Tejera et al ., ; Kyono et al ., ; Taylor et al ., ; Kamiyama et al ., ; Yang et al ., ; Kuentz et al ., ), mechanical (Tesarik et al ., ) and electrical (Dirican et al ., ; Egashira et al ., ) activations have been suggested, although spontaneous activation of the oocyte after ICSI has been reported in some cases (Lundin et al ., ; Kilani et al ., ; Stone et al ., ; Nardo et al ., ; Zeyneloglu et al ., ; Banker et al ., ; Bechoua et al ., ; Sahu et al ., ). To the best of our knowledge, as the first livebirth by ICSI from globozoospermia described in 1994, there have been only 11 livebirths achieved with globozoospermia by ICSI without assisted oocyte activation (AOA) and 15 with AOA and one by intracytoplasmic morphologically selected sperm injection (Sermondade et al ., ) were reported up to 2013.…”
Section: Introductionmentioning
confidence: 98%